Cytokine production patterns in patients with sickle cell disease and avascular necrosis of the femoral head - Fawaz Azizieh; Raj Raghupathy; Renu Gupta; Akmal Zahra; Hanan Al-Abboh; Huda Alsahhaf; Rubina Fatima; Adekunle Adekile (Pediatric Hematology Oncology Journal, 2025)
Background: An imbalance in pro- and anti-inflammatory cytokines has been suggested to contribute to tissue damage in sickle disease (SCD) following recurrent ischemia, which leads to several complications including avascular necrosis (AVN) of the femoral head. This study aimed to investigate the profiles of cytokines produced by mitogen-stimulated peripheral blood mononuclear cells (PBMC) in SCD patients with or without AVN. Methods: The patients were recruited from the outpatient hematology clinics of Mubarak al-Kabeer Hospital, Kuwait. They were screened for AVN using magnetic resonance imaging (MRI). Levels of peripheral blood mononuclear cell (PBMC)-secreted cytokines were estimated in 31 AVN-negative and 16 AVN-positive SCD patients. Four pro-inflammatory cytokines (IL-1−β, IL-6, IL-17A, and TNF-α) and three anti-inflammatory cytokines (IL-4, IL-10, and TGF-β) were assayed in a multiplex ELISA. Results: Mitogen-activated PBMCs from the patients who were AVN-positive secreted significantly higher levels of the pro-inflammatory cytokines TGF-β, and IL-4 compared to AVN-negative patients. Similarly, three ratios (IL-17A/IL-4, TNF-α/IL-4, and, IL-17/TGF-β) were significantly higher in AVN-negative, compared to AVN-positive patients, thus showing a pro-inflammatory bias in the former. The multivariate pattern plot shows that points of AVN-positive data are clustered closely, separating them from the AVN-negative data. Conclusion: Our data suggest that it may be worthwhile to explore levels and ratios of pro- to anti-inflammatory cytokines produced by mitogen-stimulated PBMC in patients with SCD with regards to prognosis and outcomes. The multivariate pattern analysis of seven cytokines revealed a pattern that can be used as a predictive tool to delineate those patients that may develop AVN.